Eugenol Improves Follicular Survival and Development During in vitro Culture of Goat Ovarian Tissue - Silva, R. F.; Lima, L. F.; Ferreira, Anna C. A.; Silva, A. F. B.; Alves, D. R.; Alves, B. G.; Oliveira, A. C.; Morais, Selene M.; Rodrigues, Ana Paula R.; Santos, Regiane R.; Figueiredo, J. R. (Frontiers in Veterinary Science, 2022)
This study aimed to evaluate the effect of adding different concentrations (10, 20 or 40 µM) of eugenol on the in vitro survival and development of goat preantral follicles. Additionally, in vitro culture was performed in the presence of the antioxidants anethole (300 µg/mL) and ascorbic acid 50 (µg/mL). Ovarian fragments from five goats were cultured for 7 days in Alpha Minimum Essential Medium (α-MEM+) either or not supplemented with eugenol (10, 20 or 40 µM; EUG 10, EUG 20 or EUG 40, respectively), ascorbic acid (50 µg/mL; AA) or anethole (300 µg/mL; ANE 300). On day 7 of culture, when compared to MEM, the addition of EUG 40 increased the rate of follicular development, as observed by a decrease in the proportion of primordial follicles concomitantly with an increase in the rate of normal developing follicles. Furthermore, EUG 40 increased significantly both follicular and oocyte diameters. All the tested antioxidants, except ANE 300, were able to significantly decrease the levels of reactive oxygen species (ROS), but EUG 40 was the most efficient to neutralize free radicals. All the ovarian tissues cultured in the presence of antioxidants, especially EUG 40, presented a significant decrease in H3K4me3 labelling, indicating a silencing of genes that play a role in the inhibition of follicular activation and induction of apoptosis. When compared to cultured control tissues, both EUG 40 and ANE 300 significantly increased the intensity of calreticulin labelling in growing follicles. The mRNA relative expression of ERP29 and KDM3A was significantly increased when the culture medium was supplemented with EUG 40 indicating a response to ER stress. In conclusion, eugenol at 40 µM improved in vitro follicle survival, activation and development, as well as decreased ROS production, ER stress, and histone lysine methylation.